(untitled) (KULT_online, 2024)
In Masculinity in Transition, K. Allison Hammer critically examines the role of normative (toxic) masculinity in fostering numerous societal ills in the United States. Hammer offers a refreshing perspective by weaving alternate forms of queer and trans masculinities into complex ideologies. Tracing normative masculinity in the contexts of racial capitalism, settler colonialism, and white supremacist fraternal bonds, Hammer emphasizes the potential politics of solidarity in unruly alliances of alternative embodiments and masculinities, while arguing for a reconceptualization of masculinity enriched by care and collaborative bonds.